Financial Data Management in Support of Tax Compliance at PT Abadi Mitra Zein - Isyfa Hasyatillah Ishaq; Herry Sutanto (Journal of Management, Entrepreneurship, and Tourism, 2026)
Financial data management is a critical element in ensuring orderly, accurate, and accountable financial administration within organizations. At PT Abadi Mitra Zein, limited human resources in the financial administration unit potentially lead to the accumulation of unprocessed transaction data and delays in tax reporting activities. This study aims to examine the financial data management process in supporting corporate tax compliance. A descriptive qualitative approach was employed through direct observation, interviews with finance personnel, and document analysis. The findings show that the company implements financial data management through four main stages, namely periodic transaction recording, data classification based on transaction type, systematic archiving of supporting documents, and preparation of financial data for tax calculation purposes. However, constraints such as limited staffing and suboptimal data management systems remain significant obstacles affecting administrative efficiency and reporting timeliness. Strengthening human resource capacity and adopting more structured financial data management systems are therefore essential to improve financial orderliness and support effective tax compliance.